CREATING AND SHAPING ENTREPRENEURIAL MIND TO FACE THE DIGITAL ERA SOCIETY - Sapto Imambachri; Sugiyarto Sugiyarto; Edi Junaedi (PENGABDIAN SOSIAL, 2022)
ABSTRACT Entrepreneurship plays a very vital role in the economic growth of a country, including  Indonesia, the role of entrepreneurship in Indonesian economy not only helps the government and society to increase per capita income, but also includes job creation for the people of Indonesia. Seeing the importance of Micro, Small and Medium Enterprises (MSMEs) to support the Indonesian economy going forward, the Government of Indonesia is aggressively continuing to improve Indonesia's infrastructure, as well as economic growth centers, such as the inauguration of the Mandalika Circuit of West Nusa Tenggara (NTB), 18 -20 March which initiated the emergence of many entrepreneurs.  Indonesia's entrepreneurship ratio is only around 3.47 percent, and this figure is quite low when compared to fellow ASEAN countries such as Singapore which reached 8.76 percent, Thailand 4.26 percent and Malaysia 4.74 percent. "Some experts say that a country can be said to be developed if it has an entrepreneur ratio of around 10-14 percent,". Looking at the size of Indonesia's population and abundant natural resources, it is certainly not impossible that Indonesia will soon become a developed country if it is supported by reliable human resources. The number of productive population aged between 25 – 54 years is quite large, which is around 113 million (42.56%), so the Indonesian market is a large market that is targeted by many countries in the world. To become a reliable entrepreneur requires high motivation and has self-confidence and dares to take business risks, has a strong leadership spirit and able to see business opportunities by looking at the life around oneself and can provide solutions to problems that are a source of community dissatisfaction by offering new ideas and effective solutions. Seeing the importance of entrepreneurship in the future which will help to make a nation progress, the Secretarial Study Program - Pamulang University in the implementation of its International Community Service (PKM) entitled "Creating and Shaping The Entrepreneurial Mind to Face the Digital Era Society"  conducted an online event on March 24, 2022 by Inviting an Entrepreneur Mr. Diwakar Saraswat CEO of Vorx Information System Pty., Ltd. which is engaged in Integrated Information system software based in Melbourne – Australia. It is hoped that with the presence of PKM regarding entrepreneurship, it will boost the interest of students, start up entrepreneurs in South Tangerang (MSMEs) who are also invited to get enlightenment about entrepreneurship. Key words : Entrepreneurship, Micro small medium enterprises, motivation  ABSTRAK Kewirausahaan memainkan peran yang sangat vital dalam pertumbuhan ekonomi sebuah negara termasuk Di Indonesia, peran wirausaha didalam perekonomian Indonesia tidak saja membantu pemerintah dan masyarakat untuk meningkatkan pendapatan perkapita, akan tetapi juga meliputi pembukaan lapangan kerja bagi masyarakat Indonesia. Melihat akan pentingnya Usaha  Mikoro kecil dan Menengah (UMKM) untuk menopang ekonomi Indonesia kedepan, maka Pemerintah Indonesia  dengan gencar terus memperbaiki infra struktur Indonesia, demikian juga dengan pusat- pusat pertumbuhan ekonomi terus digalakan seperti diresmikan Sirkuit Mandalika Nusa Tenggara Barat (NTB), 18-20 Maret  yang menginisiasi banyaknya bermunculan wirausahawan.      Rasio kewirausahaan Indonesia baru berkisar antara 3,47 persen, dan angka ini  cukup rendah bila dibandingkan dengan sesama negara ASEAN seperti Singapura yang mencapai 8,76 persen, Thailand 4,26 persen serta Malaysia 4,74 persen. "Beberapa Pakar mengatakan bahwa  bahwa suatu negara  dapat dikatakan maju apabila  mempunyai  rasio wirausahawan berkisar 10-14 persen,", kalau melihat jumlah penduduk Indonesia yang cukup besar, serta sumber daya alam yang melimpah tentunya bukan mustahil Indonesia akan segera menjadi negara maju apabila di topang sumber daya Manusia yang handal. Jumlah penduduk yang produktif berusia anta 25 – 54 tahun cukup besar yaitu sekitar 113 juta(42,56%) maka pasar Indonesia merupakan pasar yang besar yang diincar oleh banyak negara di Dunia.  Untuk menjadi seorang wirausahawan yang handal  diperlukan motivasi yang tinggi serta mempunyai kepercayan diri serta berani mengambil resiko usaha., mempunyai jiwa kepemimpinan yang kuat serta dapat melihat peluang bisnis dengan melihat kehidupan sekelilingnya serta dapat memberikan solusi terhadap masalah yang menjadi sumber ketidak puasan masyarakat dengan menawarkan pemikiran baru dan solusi yang tepat guna. Melihat penting kewirausahaan di masa mendatang yang akan membuat sebuah bangsa akan menjadi maju, maka Prodi Sekretari - Universitas Pamulang didalam pelaksanaan Pengabdian Kepada Masyarakat (PKM) Internasional nya yang berjudul “ Creating and Shaping The Entrepreneurial Mind to Face the Digital Era Society” diadakan secara Daring pada Tanggal 24  Maret 2022 Mengundang Pembicara Seorang Entrepreneur  Mr. Diwakar Saraswat CEO dari Vorx Information System Pty.,Ltd. yang bergerak dibidang Integrated Information system software berasal dari Melbourne – Australia. Diharapkan dengan hadirnya PKM Mengenai kewirausahaan, akan mendongkrak minat para mahasiswa, UMKM tangsel yang turut diundang untuk mendapat pencerahan mengenai kewirausahaan. Kata Kunci : Entreprenuership, Usaha Mikro Kecil dan Menengah, Motivasi